Different Strains of BK Polyomavirus: VP1 Sequences in a Group of Iranian Prostate Cancer Patients - Vaezjalali, Maryam; Azimi, Helia; Hosseini, Seyed Masoud; Taghavi, Afsoon; Goudarzi, Hossein (Urology Journal, 2018)
Purpose: BK virus (BKV) has a worldwide seroprevalence in humans. Based on sequences of the major capsid proteins, i.e. viral protein 1 (VP1), there are four BKV genotypes. Each genotype has its own subtypes, and was shown to be circulating independently in the human population. The aim of this study was to determine BKV genotypes and subtypes among Iranian patients with prostatic cancer, benign prostatic hyperplasia, and kidney transplantation. Materials and Methods: BKV DNA was extracted from prostatic cancers and benign prostatic hyperplasia blocks and also urine of kidney transplantation patients. BKV (VP1) gene was amplified partially (327nt) by homemade polymerase chain reactions and subjected for sequencing and phylogenetic analysis. Bioedit version 7.0 and Mega version 5.0 were used for sequence analysis and for comparing the results with world-driven BKV sequences. Results: All of BKV VP1 genes which were derived from Iranian patients were classified with subtype 1b2 strains from Germany and Turkey. Predicted amino acid sequences from the studied region of VP1 showed that all of these nucleotide diversities could change amino acid sequence numbers 60, 68, 72, 73 and 82 among VP1. Conclusion: The interesting point was that genetic analysis of derived sequences showed a different feature of genetic diversity among Iranian sequences. This feature has not been reported yet. This characteristic feature of Iranian BKV VP1 gene provides a unique cluster of sequences in phylogenetic tree.